Reflections on the Researcher-in-Residence model co-producing knowledge for action in an Integrated Care Organisation: a mixed methods case study using an impact survey and field notes. (1st May 2019) - Gradinger, Felix; Elston, Julian; Asthana, Sheena; Martin, Susan; Byng, Richard
Abstract : Background / aims / objectives 'Embedded' approaches to knowledge mobilisation are gaining currency, as health and social care services come under increasing pressure to redesign services now rather than wait for research. One such approach is the 'Researcher-in-Residence' (RiR) model which seeks to co-produce knowledge for action. The aim of this paper is to extend the evidence base regarding mechanisms of impact.Methods A two-year mixed-method case study of the experience and impact of two part-time RiRs, embedded within an Integrated Care Organisation to support the implementation of new models of care. Data included the results of an anonymous impact survey sent to 80 key stakeholders, field notes of meetings (n=112), and observations of naturally occurring events (n=68).Findings Impacts were identified in relation to use of co-produced evidence, capacity building, changes in ways of working, and to a lesser degree changes in operations or strategy. Impact involved learning which was mediated by three non-linear, non-predictable, positive and negative feedback cycles (expectations, access, learning/ improvement). A mixture of technical skills, personal attributes and behaviours were identified as key to this mediation.Discussion/conclusion The RiR model promises a timely, applied and transferable research model that contributes to the development, evaluation and adaptation of innovations that seek to integrate services where the evidence base is weak and uncertain. However, the model is not without challenges. These could be addressed by flexibility of research design and funding, and adequately supporting and developing key attributes of RiRs.